Robotic musicianship : embodied artificial creativity and mechatronic musical expression /: embodied artificial creativity and mechatronic musical expression. ([2020]) - Weinberg, Gil; Bretan, Mason; Hoffman, Guy; Driscoll, Scott
No abstract available